High Acceptability and Increased HIV-Testing Frequency After Introduction of HIV Self-Testing and Network Distribution Among South African MSM. (1st March 2018) - Lippman, Sheri A.; Lane, Tim; Rabede, Oscar; Gilmore, Hailey; Chen, Yea-Hung; Mlotshwa, Nkuli; Maleke, Kabelo; Marr, Alexander; McIntyre, James A.
Abstract : Background: South African men who have sex with men (MSM) have a high burden of undiagnosed HIV infection and HIV-testing rates incommensurate with their risk. HIV self-testing (HIVST) may increase testing uptake, frequency, and earlier HIV detection and treatment. Setting: Gert Sibande and Ehlanzeni districts, Mpumalanga Province, South Africa. Methods: We conducted a longitudinal HIVST study among MSM between June 2015 and May 2017. Overall 127 HIV-negative MSM were provided with up to 9 test kits of their choice—oral fluid or blood fingerstick—to use themselves and distribute to their networks. Surveys conducted 3- and 6-month post–enrollment elicited information on HIVST experiences, preferences, acceptability, utilization, and distribution. We used generalized estimating equations to assess changes in testing frequency. Results: Ninety-one percent of participants self-tested. All participants who self-tested reported being likely to self-test again, with over 80% preferring HIVST to clinic-based testing. Fingerstick was preferred to oral fluid tests by approximately 2:1. Returning participants distributed 728 tests to sexual partners (18.5% of kits), friends (51.6%), and family (29.8%). Six participants seroconverted during the study, and 40 new diagnoses were reported among test recipients. Frequent (semi-annual) testing increased from 37.8% before the study to 84.5% at follow-up ( P < 0.001), and participants reported anticipated frequent testing of 100% if HIVST were available compared with 84% if only clinic-testing were available in the coming year ( P < 0.01). Conclusions: HIVST use and network distribution is acceptable and feasible for MSM in South Africa and can increase testing uptake and frequency, potentially improving early detection among MSM and their networks.